Dietary Intervention, When Not Associated With Exercise, Upregulates Irisin/FNDC5 While Reducing Visceral Adiposity Markers in Obese Rats - Furino, Vanessa de Oliveira; Alves, João Manoel; Marine, Diego Adorna; Sene-Fiorese, Marcela; Rodrigues, Carla Nascimento dos Santos; Arrais-Lima, Cristina; Mattiello, Stela Márcia; Castro, Cynthia Aparecida de; Borra, Ricardo Carneiro; Rocha, Marina Campos; Malavazi, Iran; Duarte, Ana Cláudia Garcia de Oliveira (Frontiers in Physiology, 2021)
Obesity is an epidemic disease and the expansion of adipose tissue, especially visceral fat, promotes the secretion of factors that lead to comorbidities such as diabetes and cardiovascular diseases. Thus, diet and exercise have been proposed as an intervention to reverse these complications. An adipocytokine, known as irisin, mediates the beneficial effects of exercise. It has been proposed as a therapeutic potential in controlling obesity. In view of the above, this paper attempts to determine the modulation of irisin, visceral adiposity and biochemical markers in response to dietary intervention and aerobic exercise. To do this, 52 diet-induced obese male Wistar rats were divided into the following 4 groups: high-fat diet and exercise (HFD-Ex); HFD-Sedentary (HFD-Sed); chow-diet and exercise (CD-Exercise); and CD-Sed. The exercise-trained group performed a treadmill protocol for 60 min/day, 3 days/week for 8 weeks. Body mass, Body fat, body area, fat mass and fat-free mass were analyzed. Mesenteric, epididymal and retroperitoneal adipose tissue was collected and histological analysis was performed. Biochemical irisin, triglycerides, glucose, insulin and inflammatory markers were determined and, FNDC5 protein expression was analyzed. In this study, the diet was the most important factor in reducing visceral adiposity in the short and long term. Exercise was the most important factor in preserving muscle mass and reducing visceral depots after a long term. Moreover, the combination of diet and exercise can enhance these effects. Diet and exercise exclusively were the factors capable of increasing the values of irisin/FNDC5, however it did not bring cumulative effects of both interventions. Prescriptions to enhance the obesity treatments should involve reducing visceral adiposity by reducing the fat content in the diet associated with aerobic exercise.